MiR-192 attenuates high glucose-induced pyroptosis in retinal pigment epithelial cells via inflammasome modulation. Issue 4 (1st April 2022) - Gu, Cao; Zhang, Hongjun; Li, Qing; Zhao, Shaofei; Gao, Yu
ABSTRACT: Diabetic retinopathy is one of the most characteristic complications of diabetes mellitus, and pyroptosis plays acrucial role in the onset and development of diabetic retinopathy. Although microRNA-192 (miR-192) has been demonstrated to be involved in diabetic retinopathy progression, to the best of our knowledge, its potential and mechanism in cell pyroptosis in diabetic retinopathy have not been studied. The present study demonstrated that high glucose (HG) contributes to the pyroptosis of retinal pigment epithelial (RPE) cells in a dose-dependent manner. The results revealed that miR-192 was weakly expressed in HG-induced RPE cells. Furthermore, overexpression of miR-192 abrogated the role of HG in RPE cell pyroptosis. Based on the bioinformatics analysis, a dual-luciferase reporter assay, and an RNA pull-down assay, FTO α-ketoglutarate-dependent dioxygenase (FTO) was demonstrated to be a direct target of miR-192. Additionally, upregulation of FTO abolished the effects of miR-192 on RPE cells treated with HG. Nucleotide-binding domain leucine-rich repeat family protein 3 (NLRP3) inflammasome activation is vital for cell pyroptosis, and FTO functions as a pivotal modulator in the N 6 -methyladenosine modifications of various genes. Mechanistically, FTO enhanced NLRP3 expression by facilitating demethylation of NLRP3. In conclusion, the present results demonstrate that miR-192 represses RPE cell pyroptosis triggered by HG via regulation of the FTO/NLRP3 signaling pathway. GRAPHICAL ABSTRACT: uf0001